Acute effects of shorter but more frequent rest periods on mechanical and perceptual fatigue during a weightlifting derivative at different loads in strength-trained men - Jukic, I.; Tufano, J. J. (Sports Biomechanics, 2022)
Traditional sets can be fatiguing, but redistributing rest periods to be shorter and more frequent may help maintain peak vertical barbell displacement (DISP) and reduce concentric repetition duration (CRDI), peak velocity decline (PVD) and perceptual exertion (RPE) across multiple repetitions, sets and loads during clean pulls. Fifteen strength-trained men performed: 3 traditional sets of 6 clean pulls using 80% (TS80), 100% (TS100) and 120% (TS120) of power clean 1RM with 180 seconds of inter-set rest; and 3 `rest redistribution` protocols of 9 sets of 2 clean pulls using 80% (RR80), 100% (RR100) and 120% (RR120) of power clean 1RM with 45 seconds of inter-set rest. DISP was greater during RR100 (g = 0.39) and RR120 (g = 0.56) compared to TS100 and TS120, respectively. In addition, PVD was less during RR120 than TS120 (g = 1.18), while CRDI was greater during TS100 (g = 0.98) and TS120 (g = 0.89) compared to RR100 and RR120, respectively. Also, RR protocols resulted in lower RPE across the sets at all loads (g = 1.11-1.24). Therefore, RR generally resulted in lower perceptual and mechanical fatigue, evidenced by lower RPE, PVD, CRDI and greater DISP than TS, and these differences became even more exaggerated as the barbell load and the number of sets performed increased.